Modelowanie procesu czytania na potrzeby glottodydaktyki - Kulczyńska, Agnieszka (Neofilolog, 2010)
The author investigates the presence of reading models in L2 teaching theory and research. She observes that such models seem to play a rather „ornamental” role. The author is convinced, however, that effective use of reading models would bring positive results, such as facilitating communication between researchers, and more effective planning of research and teaching. The model that might be taken into consideration is that developed by the Quebecois pedagogue J. Giasson.